The Effect of Different Polishing Systems on the Surface Roughness of Nanocomposites: Contact Profilometry and SEM Analyses - Oglakci, B.; Kucukyildirim, B. O.; Ozduman, Z. C.; Dalkilic, E. Eliguzeloglu (OPERATIVE DENTISTRY INC, 2021)
The aim of this study was to evaluate the effects of different polishing systems on the surface roughness of different nanocomposite resins using various analysis methods. Three types of nanocomposite resins were investigated in this study: supra-nanohybrid (Estelite Asteria), nanohybrid (GrandioSo), and nanoceramic composite resins (Ceram-X Spheretec One). Forty- eight disc-shaped specimens (4 mm in diameter, 2 mm in thickness) were fabricated using a Teflon mold and divided into four groups according to the different polishing systems (n= 12). All specimens were processed with one of the following methods: Mylar strip (control), one-step polishers (Opti1step), two-step polishers (Clearfil TwistDia), or multistep polishers (SofLex XT Pop- on). The surface roughness (Ra, mm) was measured by contact profilometry (Mahr, Marsurf PS1) (n=10) and scanning electron microscopy (SEM) (Thermo Fisher Scientific, Phenom XL) at 400x magnification (n=2). The data were statistically analyzed using Kruskal-Wallis and Bonferroni correction tests (p 0.05). The multistep polishers created lower surface roughness than the one-step polishers for nanohybrid and nanoceramic composites. In terms of the composite resins, supra-nanohybrid composite exhibited lower surface roughness than nanohybrid composite for all polishing systems (p< 0.05). The SEM observations confirmed the surface roughness measurements related to the surface morphology. One-step and two-step polishers created porosity on the surface of nanohybrid and nanoceramic composites. EDS analysis indicated the elemental composition of the particles in the porous zones was quite close to diamond abrasives and glass fillers.
Keywords: SCANNING-ELECTRON-MICROSCOPY; ONE HYBRID COMPOSITE; ONE-STEP; RESIN COMPOSITES; COLOR STABILITY; POLISHABILITY; Dentistry, Oral Surgery & Medicine